Use of cyclical etidronate and prevention of non-vertebral fractures. - van Staa, T; Abenhaim, L; Cooper, C (1998)
This study examined the effects of cyclical etidronate, when used in routine clinical practice, on the prevention of fracture. Information was obtained from 550 general practices in the UK that provide their medical records to the General Practice Research Database. A total of 7977 patients taking cyclical etidronate treatment and 7977 age-, sex- and practice-matched control patients with a diagnosis of osteoporosis were analysed. People taking cyclical etidronate had a significantly reduced risk of non-vertebral fracture (by 20%) and of hip fracture (by 34%) relative to the osteoporosis control patients. The relative risk of non-vertebral fracture was 0.80 (95% confidence interval 0.70-0.92), that of hip fracture 0.66 (0.51-0.85) and that of wrist fracture 0.81 (0.58-1.14). When fracture incidence rates were compared between the two groups, the rate of non-vertebral, hip and wrist fracture decreased significantly (P < 0.05) with increasing etidronate exposure. The results of this study complement and extend clinical observations supporting the anti-fracture efficacy of cyclical etidronate therapy.